[18F]FB(ePEG12)12-exendin-4 noninvasive imaging of insulinoma negative for insulin immunostaining on specimen from endoscopic ultrasonography-guided fine needle aspiration: a case report with review of literature - Daisuke Otani; Takaaki Murakami; Saeko Murakami; Ikuko Hanaoka; Hiroyuki Fujimoto; Yoichi Shimizu; Kanae Kawai Miyake; Kentaro Sakaki; Yohei Ueda; Daisuke Tanaka; Tsuyoshi Ohno; Hironori Shimizu; et al. (Endocrine Journal)
Insulinomas are the most common functional pancreatic neuroendocrine neoplasm; when treatment is delayed, they induce hyperinsulinemic hypoglycemia, which is life-threatening. As surgical resection is the only curative treatment for insulinoma, preoperative localization is crucial; however, localization based on conventional imaging modalities such as computed tomography (CT) and magnetic resonance imaging is often inconclusive. Somatostatin receptor-targeted imaging is another option for detecting pancreatic neuroendocrine neoplasms but has low sensitivity and is not specific for insulinoma. The clinical application of other localizing approaches such as selective arterial calcium stimulation and endoscopic ultrasonography-guided fine needle aspiration (EUS-FNA) is limited by their being invasive and/or technically complex. Moreover, an EUS-FNA specimen of an insulinoma may be negative on insulin immunostaining. Thus, a noninvasive and clinically practical insulinoma-specific diagnostic tool to discriminate insulinomas with high accuracy is anticipated. Glucagon-like peptide-1 receptor (GLP-1R)-targeted imaging has emerged in the effort to fulfill this need. We recently developed the novel fluorine-18-labeled exendin-4-based probe conjugated with polyethylene glycol, [18F]FB(ePEG12)12-exendin-4 (18F-exendin-4) for positron emission tomography (PET) imaging and reported its clinical benefit in a case of insulinoma in the pancreatic tail. We report here a case of insulinoma in the pancreatic head in which an EUS-FNA specimen was negative on insulin immunostaining while precise preoperative localization and conclusive evidence for curative enucleation was provided by 18F-exendin-4 PET/CT (Japan Registry of Clinical Trials; jRCTs051200156).